Pengembangan Aplikasi Ujian Berbasis Website Pada SMK AR-RAHMA CIDAHU Menggunakan HTML5 dan PHP Signature Pad - Ikhsan Ma'arif (Universitas PGRI Yogyakarta, 2022)
This study aims to analyze the needs, design and develop an online exam application used at SMK AR-RAHMA CIDAHU, the method used in this development is the ADDIE Model which consists of five stages namely Analy-sist, Design, Development, Implementation, and Evaluation. SMK AR-RAHMA CIDAHU is one of the schools that implements an online exam system using a website-based application during the pandemic, but the exam application used has shortcomings to adjust the needs of adminis-trative staff, one of which is the attendance feature. In this case, application development is carried out by add-ing a digital attendance feature using the HTML5 function and PHP Signature Pad with digital signature output stored in image format. The development of these features can be used as evidence of the presence of examinees to support the reporting of test results as well as to improve the usability of the application itself.